Is India In Win-Win Situation W.R.T. ASEAN Bilateral Trade? (Journal of Namibian Studies : History Politics Culture, 2023)
In the wake of the end of the cold war in the year 1991  and the collapse of socialist ideology, India started to have a liaison with the USA and its collaborating countries such as South Korea, South east countries. Country’s demand augmented to open the doors of the economy and enhance trade with overseas countries to safeguard the country from the wrenching Balance of Payment crisis. India started to build relations with neighboring countries to strengthen the EXIM policy. So India announced ‘Look East Policy’ in the year 1992 to explore the resources of north eastern states and bring regional balance. But by seeking China's dominance over South east asian countries created threat in our Indian ocean so we shifted from diplomatic, “Look East Policy” to most strategic “ Act East Policy”. The significance of SouthEast Asia to India in the fields of  economy, polity, social, defence, maritime trade, and security dimensions so that ASEAN holds a prominent position as India's fourth-largest trading partner. Bilateral trade in which ASEAN countries gained phenomenally as their exports are more than imports through Free Trade Agreement. Despite all India’s to and fro trade with ASEAN is of non-oil and non-mineral product which is a significant achievement and showcases the trade integrity. India’s import of textiles, electronic goods, chemicals, and machinery are vital for its manufacturing and service sector which portrays a good sign of trade. Lastly to enhance the trade, India needs to diversify the export effectively. Thus India will be in a Win-Win situation from bilateral trade with ASEAN countries.